Aura in Cluster Headache: A Cross‐Sectional Study - Coo, Ilse F.; Wilbrink, Leopoldine A.; Ie, Gaby D.; Haan, Joost; Ferrari, Michel D. (Headache, 2018)
Background Aura symptoms have been reported in up to 23% of cluster headache patients, but it is not known whether clinical characteristics are different in participants with and without aura. Methods Using validated web‐based questionnaires we assessed the presence and characteristics of attack‐related aura and other clinical features in 629 subjects available for analysis from an initial cohort of 756 cluster headache subjects. Participants who screened positive for aura were contacted by telephone for confirmation of the ICHD‐III criteria for aura. Results Typical aura symptoms before or during cluster headache attacks were found in 44/629 participants (7.0%) mainly involving visual symptoms (61.4%). Except for lower alcohol consumption and higher prevalence of frontal pain in participants with aura, no differences in clinical characteristics were found compared with participants without aura. Conclusion At least 7.0% of the participants with cluster headache in our large cohort reported typical aura symptoms, which most often involved visual symptoms. No major clinical differences were found between participants with and without aura.